FUNCTIONAL CLASS OF CHRONIC HEART FAILURE AND CLINICAL FEATURES OF PATIENTS WITH PERMANENT PACEMAKERS - Kolomytseva, I. M.; Volkov, D. E.; Lopin, D. A.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The study included 162 patients (89 men and 73 women) aged 69 ± 10 years who underwent permanent pacing about atrio-ventricular block, permanent atrial fibrillation and sick sinus node syndrome with pacing modes DDD/DDDR and VVI/VVIR as well as chronic heart failure (CHF) with cardiac resynchronization therapy (CRT-P and CRT-D). Clinical features of patients were evaluated according to the functional class (FC) CHF. Patients with pacemakers the most frequent had II and III CHF FC which more often associated with myocardial infarction, stable angina, diabetes mellitus, atrial fibrillation, stage IIA and IIB CHF. It is concluded that patients with ECS require optimization of medical interventions.